Performance of rice variety P 1460 in front line demonstrations under rainfed conditions in Southern humid region of Rajasthan - Singh, Teekam; Singh, Ranjeet; Soni, R.L. (Annals of Agricultural Research, 2014)
The study was conducted at Krishi Vigyan Kendra, Banswara in Southern Humid Agro-climatic Zone of Rajasthan (Zone IV b) for three consecutive rainy seasons of 2009, 2010 and 2011 to evaluate the performance of basmati type rice variety "Pusa 1460" at farmers field under rainfed conditions. Front line demonstrations (FLDs) were conducted with scientific package of practices of rice technology. The Pusa 1460 variety of rice was found superior over farmers’ existing practices with local landraces. Pusa 1460 with improved production technologies followed in FLDs, increased mean grain yield by 28.7% over existing farmers’ practice with only Rs. 1511/ha extra expenditure on inputs. The mean extension gap (0.57 t/ha) and mean IBCR (3.94) are sufficiently high to motivate farmers for adoption of Pusa 1460 and rice production technology.